Depolymerization of lignin using a solid base catalyst - Chaudhary, Richa; Dhepe, Paresh L. (Energy & Fuels, 2019)
Lignin extraction from lignocellulosic biomass has attracted considerable attention for an alternative production of sustainable fuels and chemicals. We report the lignin isolation from coconut coir using Klason, organosolv, and soda methods and the depolymerization of isolated lignin to value-added chemicals using a solid base catalyst. The yield of isolated lignin by the Klason method was found to be about 4 to 6 times higher than that by other methods. The structure of isolated Klason lignin (CC-KL), organosolv lignin (CC-ORGL), and soda lignin (CC-SL) was studied using attenuated total reflection (ATR), NMR, microanalysis, and so forth. The monomer molecular formula derived from microanalysis suggested that coir lignin is rich in guaiacyl units. ATR and C-13 NMR clearly indicate that CC-ORGL contains more C-C bonds compared to CC-KL and CC-SL. Subsequently, these isolated lignins were depolymerized over a solid base catalyst (NaX) under atmospheric pressure. CC-SL shows a high yield of aromatic products (28%) compared to CC-ORGL and CC-KL. In order to develop a sustainable future technology, one-pot depolymerization of coconut coir was performed which resulted in a high yield (64%) of aromatic products.